PENGGUNAAN MEDIA CHEM PUZZLE UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 4 PEKANBARU - Sri Kurniati; Erviyenni Erviyenni; Johni Azmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research aims to increase student learning achievement on the topic of hydrocarbons in class X Senior High School (SMAN) 4 Pekanbaru. Media Chem Puzzle is adapted to the topic of hydrocarbons. The research is a kind of experiment research with pretest-posttest design. The samples of this research were the students of class X4 as the experimental class and students of class X7 as the control class. Experimental class is a class that is used to media Chem Puzzle while the control class was not. Data analysis technique used is the t-test. Based on data analysis of data obtained tcount> ttable is 3,74>1.67, means that the use of Chem Puzzle can improve student learning achievement on the topic of hydrocarbons in class X Senior High School (SMAN) 4 Pekanbaru. The category improvement of student achievement at experiment class was high category with N-gain normalized is 0,79. Meanwhile, the category improvement of student achievement in control class was medium category with N-gain normalized is 0,64.Keywords :Achievement, Chem Puzzle, Hydrocarbons